WiFi/WiMAX seamless convergence with adaptive vertical handover for continuity of Internet access - Saeed, Rashid Abdelhaleem; Mohamad, Hafizal; Abbas, Mazlan; Mohd Ali, Borhanuddin (Scientific Research Publishing, 2011)
The next generation of the wireless networks will consist of several overlapping tiers. Provision of undisrupted communication to mobile users is a challenging task. Handover delay is one of the problematic issues that users are faced in the heterogeneous networks. However, in the case of both the WiMAX and the WiFi technologies which are located at the same base station (BS), the vertical handover (VHO) delay will be less as compared with the two conventional WiMAX/WiFi heterogeneous networks with two different wireless Internet service providers (WISP). Nevertheless, protocol conversion is still adding delay and jitter for data exchange between the needed two technologies. In this paper, in order to reduce the delay in the protocol conversion, a new industrial design for WiWi (WiMAX and WiFi) adaptation layer is proposed. The realization of the interworking between these two standards is discussed and evaluated. The results show that the proposed scheme-with the scenario under study- has better performance than other related works.